Preparation and Characterization of WS(2)@SiO(2) and WS(2)@PANI Core-Shell Nanocomposites - Sade, Hagit (Nanomaterials (Basel), 2018)
Two tungsten disulfide (WS(2))-based core-shell nanocomposites were fabricated using readily available reagents and simple procedures. The surface was pre-treated with a surfactant couple in a layer-by-layer approach, enabling good dispersion of the WS(2) nanostructures in aqueous media and providing a template for the polymerization of a silica (SiO(2)) shell. After a Stöber-like reaction, a conformal silica coating was achieved. Inspired by the resulting nanocomposite, a second one was prepared by reacting the surfactant-modified WS(2) nanostructures with aniline and an oxidizing agent in an aqueous medium. Here too, a conformal coating of polyaniline (PANI) was obtained, giving a WS(2)@PANI nanocomposite. Both nanocomposites were analyzed by electron microscopy, energy dispersive X-ray spectroscopy (EDS) and FTIR, verifying the core-shell structure and the character of shells. The silica shell was amorphous and mesoporous and the surface area of the composite increases with shell thickness. Polyaniline shells slightly differ in their morphologies dependent on the acid used in the polymerization process and are amorphous like the silica shell. Electron paramagnetic resonance (EPR) spectroscopy of the WS(2)@PANI nanocomposite showed variation between bulk PANI and the PANI shell. These two nanocomposites have great potential to expand the use of transition metals dichalcogenides (TMDCs) for new applications in different fields.